Tracking of Land Reclamation Activities Using Landsat Observations—An Example in Shanghai and Hangzhou Bay - Yuming Shi; Chengquan Huang; Shuo Shi; Jianya Gong (Remote Sensing, 2022)
At present, reclamation—changing ocean areas into inland land cover type for human usage—is one of the major methods for expanding land area around the world to alleviate the problem of land shortage. Thus, reclamation activities play an important role in land area extension. In recent years, reclamation projects have been active in eastern China. However, research on how to determine the initiation of reclamation activity remains very limited. Thus, a method of tracking reclamation activities was proposed in this study to analyze the coastline change due to human activities in Shanghai Lingang New City and Hangzhou Bay area. First, the reclamation area was extracted and separated into sea filling and sea enclosing. Next, the “SEDIMENT” signal track method and the “Eight-Neighborhood” morphological method were used to track dissimilar reclamation types. The historical reclamation activities (including start time and end time) over the recent 30 years were also tracked and obtained. Experimental results indicated that the time tracker accuracy of reclamation activity can reach 83.8%. Thus, this study can provide a reference for tracking coastline change.